Translational insights from EAE models : decoding MOGAD pathogenesis and therapeutic innovation - Zhang, Yanjia; Li, Dong (Frontiers in Immunology, 2025)
Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disease (MOGAD) is a rare acquired demyelinating syndrome manifesting as optic neuritis (ON), transverse myelitis (TM), acute disseminated encephalomyelitis (ADEM), and brainstem encephalitis. The disease is characterized by serum autoantibodies targeting myelin oligodendrocyte glycoprotein (MOG), which is exclusively expressed on central nervous system (CNS) myelin and oligodendrocyte membranes. Experimental autoimmune encephalomyelitis (EAE) models have been instrumental in elucidating how these antibodies trigger complement-dependent cytotoxicity (CDC) and antibody-dependent cellular responses, leading to inflammatory demyelination. With most patients experiencing relapses and approximately 50% developing permanent disabilities, therapeutic strategies focus on reducing relapse frequency and severity. MOG-EAE models have directly informed acute treatment approaches including corticosteroids, plasma exchange (PLEX), and intravenous immunoglobulin (IVIG). Mechanistic studies in MOG-EAE models have revealed complex treatment responses and identified several translational targets, including complement inhibition, B-cell depletion strategies, and cytokine-directed therapies that are now advancing to clinical trials. Current immunosuppressive therapies include azathioprine (AZA), mycophenolate mofetil (MMF), and rituximab (RTX), with their differential efficacy in MOGAD versus MS and AQP4-NMOSD now explained by EAE model findings on distinct immunopathological mechanisms. Guided by EAE translational insights into MOGAD pathophysiology, ongoing clinical trials are evaluating novel targeted therapies including complement inhibitors, plasma cell-depleting agents, and antigen-specific tolerization approaches. These EAE-derived mechanistic insights are critical for developing personalized treatment strategies that address the unique immunopathology of this challenging condition.